THE USE OF VISUAL PSYCHOTECHNIQUES TO ACTUALIZE COGNITIVE ACTIONS OF PRIMARY SCHOOL CHILDREN WITH MILD MENTAL RETARDATION - Kharchenko, Yevhen; Onufriieva, Liana (My University, 2025)
Purpose. The purpose of this article is to describe the use of visual psychotechniques to actualize cognitive actions of primary school children with mild mental retardation. Methods. The following theoretical methods of the research were used to solve the tasks formulated in the article: a categorical method, structural and functional methods, the methods of the analysis, systematization, modeling, generalization. The experimental method was the method of organizing empirical research. Results. We proved, that all mentally retarded children are characterized by reduced activity of mental processes and a weak regulatory role of thinking and speech. Mentally retarded children of primary school age with intellectual disorders usually perform activity without listening to instructions, without understanding the goals and tasks, without having an internal plan of actions, and their actions are always accompanied by weak self-control of cognitive activity. The perception and understanding of educational material by children of primary school age with intellectual disorders are inextricably linked with the characteristics of their memory. The main memory processes are preservation and memorization and storage. So, mentally retarded children have some of their own specific features, since they are formed under conditions of abnormal personal development. Conclusions. Primary school children with intellectual disabilities better remember external perceived signs. It is more difficult for them to understand and remember internal logical connections and schemes. Mentally retarded children later than their normal peers, arbitrarily memorize educational material, which is still being formed, while the advantage of deliberate memorization in mentally retarded children is expressed as clearly as in schoolchildren with normal intelligence. The greatest problems are currently caused by the reproduction of verbal material by primary school children with intellectual disabilities. The mediated sensory memory of mentally retarded children is also poorly developed.

Метою статті є описати особливості використання візуальних психотехнік з метою актуалізації пізнавальних дій дітей молодшого шкільного віку з легкою розумовою відсталістю. Методи. Для розв’язання поставлених у роботі завдань використовувалися такі теоретичні методи дослідження: категоріальний, структурно-функціональний, аналіз, систематизація, моделювання, узагальнення. Експериментальним методом є метод організації емпіричного дослідження. Результати. Доведено, що усі розумово відсталі діти характеризуються зниженою активністю розумових процесів та слабкою регулюючою роллю мислення і мовлення. Розумово відсталі діти молодшого шкільного віку з інтелектуальними розладами, зазвичай, виконують роботу, не слухаючи інструкції, не розуміючи мети і завдання, не маючи внутрішнього плану дій, а їхні дії завжди супроводжуються слабким самоконтролем пізнавальної діяльності. Сприйняття та розуміння навчального матеріалу дітьми молодшого шкільного віку з інтелектуальними розладами нерозривно пов’язані з особливостями їхньої пам’яті. Основні процеси пам’яті – збереження та запам’ятовування та зберігання – у розумово відсталих дітей мають деякі свої специфічні особливості, оскільки вони формуються за умов аномального особистісного розвитку. Висновки. Діти молодшого шкільного віку з інтелектуальними розладами краще запам’ятовують зовнішні ознаки, що сприймаються. Їм складніше зрозуміти та запам’ятати внутрішні логічні зв’язки та схеми. Розумово відсталий пізніше, ніж його нормальні однолітки, довільно запам’ятовування освітній матеріал, який все ж таки формується, тоді як перевага навмисного запам’ятовування у розумово відсталих дітей виражена так яскраво, як і у школярів із нормальним інтелектом. Найбільші проблеми наразі викликані відтворенням дітьми молодшого шкільного віку з інтелектуальними розладами словесного матеріалу. Опосередкована чуттєва пам’ять розумово відсталих дітей також є слабо розвиненою.
Keywords: visual psychotechniques; cognitive actions; mild mental retardation; intellectual disabilities; internal logical connections; deliberate memorization; normal intelligence; weak self-control of cognitive activity